Short-term effects of light quality, nutrient concentrations and emersion on the photosynthesis and accumulation of bioactive compounds in Pyropia leucosticta (Rhodophyta) - Vega, Julia; Moreira, Bruna R.; Avilés-Benítez, Antonio; Bonomi-Barufi, José; López-Figueroa, Félix (Elsevier, 2024)
Intertidal macroalgae have developed adaptation and acclimation strategies protecting against stressful environments. The red algae, Porphyra sensu lato are well known for their use as human food, but they also present potential applications in cosmeceutics. In order to enhance the content of interested bioactive compounds, this study evaluated the effects of three different stress factors, through two bi-factorial experiments, the combination of PAR and PAR supplemented by UV-A, Violet and Blue radiation (PARUVAViBl+) with three nutrient concentrations or emersion/immersion conditions. Interactive effects of PARUVAViBl+ and nutrient concentrations on the daily integrated electron transport rate (ETRint) was observed. This suggests a photoprotective effect of nitrate against the possible damage by UV-A radiation. The emersion produced a decreased in the in situ ETR, followed by a recovery during re-hydration. The energy dissipation rate (EDR), firstly described in this work, increased under nutrient limitation and under PARUVAViBl+ radiation, as a photoprotection mechanism. At morphological level, the surface/volume (S/V) ratio of the cells increased under nutrient limitation favoring the nitrogen assimilation, although it could be a risk of photodamage under UV-A radiation. Biliproteins and mycosporine-like amino acids (MAAs) increased under high nutrient availability as it was expected due to both are N-compounds. Polyphenols were higher under PARUVAViBl+ at day 2, indicating a photoprotective mechanism whereas this effect disappeared at day 7 of culture. Emersion seems to induce MAAs accumulation under PARUVAViBl+ radiation. Antioxidant capacity determined by ABTS assay was positively correlated to antioxidant substances as biliproteins, polyphenols and MAAs. The application of short-term stress conditions (2–7 days) during culture, can be a strategy to increase the content of interesting compounds due to both UV screen properties and antioxidant capacity.
Keywords: Proteínas; Algas; Rayos ultravioletas; Cosmética; Biliproteins; Blue and violet light; Emersion; Integrated electron transport rate; Mycosporine-like amino acids; Ultraviolet A radiation